(untitled) (Global Journals of Research in Engineering, 2011)
The exploratory survey of geochemical aspects of underground water resource in Ehime Mbano area of Imo State South-eastern Nigeria has been carried out. Since the creation of Ehime Mbano Local government area in 2001, there is the need for sub surface water quality assessment since the surface water has been polluted due to population explosion. The study was carried out by acquiring geologic and topographic maps of the area for easy identification of sample population areas, and to identify geological boundaries. Spring outcrops, landuse elements, especially waste dump sites and agricultural projects were visited and examined. A total of 6 water samples, 2 from springs and 4 from boreholes were collected randomly and analysed. Analysis was carried out using atomic absorption spectroscopy for major cations. Heavy metal analysis was undertaken using spectrophotometer, potassium was determined using flame photometer method, concentration of total iron (Fe2+) was determined calorimetrically using spekker absorption meter, while total dissolved solids (TDS) was determined using glass fiber filter. Turbimetric method was used to assess turbidity. Physical parameters like ph and dissolved oxygen were measured insitu in the field with appropriate standard meters. The result of geochemical survey shows that the water has high turbidity, high iron, slightly acidic, soft , portable and suitable for domestic, industrial and irrigation purposes. Above all the water has no bacteria presence, no heavy metals also no laxative effect. The average pollutional index of 2.50 indicates a slight pollution though Ezeoke Nsu area (NE) is highly polluted. Remediation to the problems of slight water pollution is proposed.